Economic Performance and Political Choice in Ukraine - Slukhai, Sergii; Slukhai, Nataliia; Bazhenova, Olena (Ekonomika, 2022)
In this article the economic performance as a factor that determined the political choice of Ukrainians has been analyzed. It is proven by a panel model that, unlike the countries with developed democracies, a retrospective economic vote in presidential elections was not observed in Ukraine; it turned out to be prospective instead with regard to the last (year 2019) presidential election. The authors presented a set of reasons which could explain such situation: lack of democratic experience, relying on heuristics and emotions, low public mood among the others. It has been demonstrated that Ukrainians’ political choice in 2019 has some consequences for the economy, which may contribute to the loss of a nation’s development guidelines for a certain period of time and subsequent social disappointment.